Biosci. J. 2016
DOI: 10.14393/bj-v32n1a2016-33302
|View full text |Cite
|
Sign up to set email alerts
|

New-record of the bush dog speothos venaticus in a human-altered landscape in west Minas Gerais, Brazil

Abstract: ABSTRACT:The bush dog (Speothos venaticus) is a Neotropical canid with a wide geographic distribution.Although globally listed as Near Threatened, this species was listed as Vulnerable in a recent assessment by the Brazilian government. Few records of this mammal have been reported in the Brazilian Cerrado, and it is considered extinct in several localities as a result of human landscape fragmentation. The record presented here is the first evidence of bush dog presence in the West of Minas Gerais, Brazil, whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
6
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 15 publications
1
6
0
2
Order By: Relevance
“…This may also be the case for other rare and threatened Brazilian species (e.g. bush dogs were recently recorded in our study area, where the species was expected but had not previously been observed; Azevedo et al, 2016). Our results suggest that road-kills and poaching, in addition to habitat loss, continue to threaten the giant armadillo in central Brazil.…”
Section: Discussionsupporting
confidence: 62%
“…This may also be the case for other rare and threatened Brazilian species (e.g. bush dogs were recently recorded in our study area, where the species was expected but had not previously been observed; Azevedo et al, 2016). Our results suggest that road-kills and poaching, in addition to habitat loss, continue to threaten the giant armadillo in central Brazil.…”
Section: Discussionsupporting
confidence: 62%
“…Esse fato se dá possivelmente devido à grande área de vida dos grupos sociais e ao hábito semifossorial, com uso de tocas como refúgio, além de apresentar populações pequenas e de baixa densidade (FERREIRA et al, 2015). Portanto, pouco se sabe sobre a distribuição geográfica e a ecologia da espécie em detalhe, apesar de alguns avanços no conhecimento nos últimos anos (AZEVEDO et al, 2016).…”
Section: Introductionunclassified
“…Portanto, o presente estudo objetiva descrever o primeiro registro do cachorrovinagre para o estado, expandindo assim a área de Misiones (Corredor Verde da Mata Atlântica) e a norte com o estado de Santa Catarina, no Brasil. Com 17,491 ha, o PET compreende a maior área contínua conservada do ecossistema da Floresta Estacional Decidual no estado do Rio Grande do Sul (BALBINOT et al, 2016). O clima predominante na região é classificado como Cfa -Clima Subtropical, segundo a classificação climática de Köppen-Geiger, com temperatura média anual de 19,5ºC (SILVA et al, 2005).…”
Section: Introductionunclassified
“…The bush dog Speothos venaticus occurs in Central and South America (DeMatteo & Loiselle, 2008), is a strict carnivore (Beisiegel & Zuercher, 2005; Lima et al, 2009) and is considered the smallest and most social Neotropical canid (Azevedo et al, 2016; Oliveira et al, 2018). Previous research has examined the conservation status, distribution and ecological requirements of this species (DeMatteo & Loiselle, 2008; Oliveira, 2009; Michalski, 2010; Ferreira et al, 2015; Lima et al, 2015; Jorge et al, 2018).…”
mentioning
confidence: 99%
“…Previous research has examined the conservation status, distribution and ecological requirements of this species (DeMatteo & Loiselle, 2008; Oliveira, 2009; Michalski, 2010; Ferreira et al, 2015; Lima et al, 2015; Jorge et al, 2018). Nevertheless, because of its elusive behaviour, low density, fragmented occurrence and large home range, the biology of the bush dog is poorly known (DeMatteo & Kochanny, 2004; Michalski & Pérez, 2005; DeMatteo & Loiselle, 2008; Lima et al, 2012, 2015; Azevedo et al, 2016; Tiepolo et al, 2016; Jorge et al, 2018; Oliveira et al, 2018).…”
mentioning
confidence: 99%